PREDICTION OF GOODS STOCK SYSTEM IN SANTI ELECTRONIC SHOP WITH DOUBLE MOVING AVERAGE METHOD - Fita Sari; Rizky Fauziah; Hommy Dorthy EIIyany (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract : Santi Electronic Store is one of the shops that sells the needs of electronic products for the community. This store requires predictions that can estimate the number of items to be sold, this shop often experiences a shortage of electronic products that will be purchased by customers. In designing the system using the Double Moving Average (DMA) forecasting method to support decisions in determining the amount of stock of electronic products to be sold for the next month. This forecasting application is made using Visual Basic Net 2010 programming language with Microsoft Office Access database. From making the system an application can be produced that can control optimal and economical demand and with a high level of accuracy and can predict the number of requests for electronic products in the coming period at the Santi Electronic Store so that the forecast results can help trading businesses so that stock does not occur requests for electronic products at the Santi Electronics Store.               Keywords : Hole; Multiple Moving Average; Prediction. Abstrak : Toko Elektronik Santi merupakan salah satu toko yang menjual kebutuhan produk elekronik bagi masyarakat. Toko ini memerlukan prediksi yang bisa memperkirakan jumlah barang yang akan dijual, pada Toko ini sering mengalami kurangnya persediaan produk eIekronik yang akan dibeIi peIanggan. Dalam perancangan sistem menggunakan metode peramalan DoubIe Moving Average (DMA) untuk proses pendukung keputusan dalam menentukan jumlah stok produk elekronik yang akan dijual untuk buIan berikutnya. Aplikasi Peramalan ini dibuat menggunakan bahasa pemrograman visualbasic net 2010 dengan database microsoft office acces. Dari pembuatan sistem dapat dihasilkan sebuah aplikasi yang dapat mengendalikan permintaan yang optimal dan ekonomis dan dengan tingkat akurasi yang tinggi serta dapat memprediksi jumlah permintaan produk elekronik pada periode yang akan datang di Toko Elektronik Santi sehingga hasil prakiraan peramalan tersebut dapat membantu usaha dagang agar tidak terjadi kehabisan stok permintaan produk elektronik pada Toko Elektronik Santi. Kata kunci : Multiple Moving Average; Prediksi; Permintaan.